2012
DOI: 10.2106/jbjs.j.01830
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Complications of the Latarjet Procedure

Abstract: The overall complication rate of 25% is higher than that reported in the literature. Although most of these complications resolved completely, two patients continued to have residual neurologic symptoms. Patients should be informed of the risk of complications associated with the Latarjet procedure, although most of the potential complications will resolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
229
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(247 citation statements)
references
References 19 publications
11
229
0
7
Order By: Relevance
“…38 Reported short-term complications after the Latarjet procedure include infection, hematoma, intraoperative graft fracture, graft malposition or malunion, nonunion, hardware complications including screw breakage, and neurovascular injury. 38 Iatrogenic neurologic injuries are possibly the most concerning, given that clinically detectable transient axillary or musculocutaneous nerve deficits have been reported postoperatively in up to 20.6% of Latarjet procedures with intraoperative nerve monitoring alert episodes occurring in 76.5% of cases. 39 Late coracoid graft resorption after Latarjet procedures is also increasingly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…38 Reported short-term complications after the Latarjet procedure include infection, hematoma, intraoperative graft fracture, graft malposition or malunion, nonunion, hardware complications including screw breakage, and neurovascular injury. 38 Iatrogenic neurologic injuries are possibly the most concerning, given that clinically detectable transient axillary or musculocutaneous nerve deficits have been reported postoperatively in up to 20.6% of Latarjet procedures with intraoperative nerve monitoring alert episodes occurring in 76.5% of cases. 39 Late coracoid graft resorption after Latarjet procedures is also increasingly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…This fact did not reach any statistical significance, so this could not be treated as any conclusion, however it could be only our suspicion that combination of technical fault and cannulated screws could increase the risk of graft fracture. Shah et al reported using canulated screws as a risk factor [16]. Three cases of recurrency in each group constituted 6.2% in OPEN and [24].…”
Section: Complications Recurrence and Revisionsmentioning
confidence: 99%
“…Recurrent instability rates following the Latarjet procedure range from 2.9% to 8%. [47][48][49][50][51] . Reported complication rate though is high (25% to 30%) with non/fibrous union, neurological injury, recurrence and infection accounting for the majority.…”
Section: Operative Management Of Complicated Anterior Instability Glementioning
confidence: 99%
“…Reported complication rate though is high (25% to 30%) with non/fibrous union, neurological injury, recurrence and infection accounting for the majority. 47,48 . A modification of the Latarjet procedure is to rotate the coracoid bone block 90 degrees to produce a 'congruent arc' bone block.…”
Section: Operative Management Of Complicated Anterior Instability Glementioning
confidence: 99%